Review Analysis of Animated Test Questions Towards Understanding Concepts in Physics Learning - Sari, Nurul Fadillah; Mufit, Fatni; Hidayanti, Hidayanti; Dwiridal, Letmi (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2023)
This study aims to (1) Analyze the application used for making animated test questions. (2) Analyzing the use of animated test questions based on education level. (3) Analyzing the use of animated format test questions based on physics learning materials. (4) Analyzing the use of animated test questions on students' understanding of physics concepts. This study uses a systematic review method using 16 national and international journal articles from 2010-2022. The results of this study showed that: (1) The application used to make test questions in animation format is very large, but Macromedia Flash is more often used. (2) Animation test questions are widely applied or used at the Senior High School level. (3) For material in physics learning, animated test questions are more often applied to the concept of light refraction. (4) Animation test questions can help students to improve their understanding of concepts. The study results show that the animated format test questions affect students' conceptual understanding. However, in reality, when carrying out the test, the format of the questions presented is still in the form of a paper, and a test is in the form of an arguments. Teachers do not know how the influence of the use of animated test questions on students' understanding of concepts, as well as what applications can be used in making animated test questions